The Influence of Health Education Using Lecture and Leaflet Methods on the Knowledge of Toddler Posyandu Cadres About Stunting Prevention in Children: Pengaruh Edukasi Kesehatan Menggunakan Metode Ceramah dan Leaflet Terhadap Pengetahuan Kader Posyandu Balita Tentang Pencegahan Stunting Pada Anak - Vivin Oktari; Isnawati Hadi, Selasih Putri Isnawati Hadi; Prabandari, Febry Heldayasari (LPPM STIKES Guna Bangsa, 2024)
The high incidence of stunting is a concern for the government. Stunting is a problem that has not yet been resolved in Indonesia. Stunting is a form of growth failure and the factor of stunting is a lack of nutritious food intake which has an impact on children's intelligence, susceptibility to disease, decreased productivity. The aim of this research is to determine the effect of health education using lectures and leaflets on the knowledge of toddler posyandu cadres about preventing stunting in children in Tridadi Village. This type of research uses a quantitative approach. In this study, a group of health posyandu cadres registered in the Tridadi Village data were given stunting knowledge education using leaflets. The population in the research of female cadres in Tridadi village, Sleman sub-district, Sleman district, Yogyakarta province totaled 69 people. The sample studied was 36 people. This research uses purposive sampling. This research instrument uses a questionnaire in the form of a structured statement. The research results showed that there was an influence before and after being given health education using leaflet media on the knowledge of toddler posyandu cadres about preventing stunting in children, namely the lecture and leaflet groups had an increase from pre to post, namely 3.73% and the lecture group had an increase from pre to post, namely 2.17%. There is an average effect of health education using leaflet media on the knowledge of toddler posyandu cadres about preventing stunting in children with a P-Value of 0.000.